ChemInform Abstract: Two Directions in Spiroheterocyclization of 1H‐Pyrrole‐2, 3‐diones upon the Action of 3‐Arylamino‐1H‐inden‐1‐ones. Issue 16 (28th March 2013) - Dmitriev, M. V.; Silaichev, P. S.; Aliev, Z. G.; Aldoshin, S. M.; Maslivets, A. N.
Abstract The different mechanisms leading to both spiroheterocycles (III) and (IV) are discussed briefly.